2023
DOI: 10.1002/bab.2469
|View full text |Cite
|
Sign up to set email alerts
|

An insight into microbial sources, classification, and industrial applications of xylanases: A rapid review

Abstract: Endo 1,4‐β‐d‐xylanases (EC3.2.1.8) are one of the key lignocellulose hydrolyzing enzymes. Xylan, which is present in copious amounts on earth, forms the primary substrate of endo‐xylanases, which can unchain the constituent monosaccharides linked via β‐1,4‐glycosidic bonds from the xylan backbone. Researchers have shown keen interest in the xylanases belonging to glycoside hydrolase families 10 and 11, whereas those placed in other glycoside hydrolase families are yet to be investigated. Various microbes such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…Xylanases, key enzymes in lignocellulose hydrolysis, which are responsible for the hydrolysis of the 1,4‐β‐xylosidic linkages of xylan and have wide applications in the food, feed, paper and cellulose industries (Angural et al., 2023 ; Kaur et al., 2023 ; Qeshmi et al., 2020 ; Suchova et al., 2022 ). The supplementation of xylanase catalyses the depolymerization of the xylan into shorter chains in food or feed, changing its chemical structure and impacting the digestive physicochemical properties and which may lead to alterations on intestinal health parameters, especially in the composition and diversity of the intestinal microbiota (Dahiya et al., 2020 ; Jiang et al., 2005 ; Moita & Kim, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Xylanases, key enzymes in lignocellulose hydrolysis, which are responsible for the hydrolysis of the 1,4‐β‐xylosidic linkages of xylan and have wide applications in the food, feed, paper and cellulose industries (Angural et al., 2023 ; Kaur et al., 2023 ; Qeshmi et al., 2020 ; Suchova et al., 2022 ). The supplementation of xylanase catalyses the depolymerization of the xylan into shorter chains in food or feed, changing its chemical structure and impacting the digestive physicochemical properties and which may lead to alterations on intestinal health parameters, especially in the composition and diversity of the intestinal microbiota (Dahiya et al., 2020 ; Jiang et al., 2005 ; Moita & Kim, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium solani is a candidate for the production of extracellular xylanases. There have been few reports on the efficient production of xylanases and exploratory studies about its xylanolytic activity [14] and optimization of enzyme production [15,16]. In a previous study, Fusarium solani was isolated from bean crops, identified, and selected from a group of one hundred and three fungal isolates for its notable ability to produce extracellular xylanases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Xylooligosaccharides (XOSs) are oligomers composed of β-D-xylopyranosyl (xylose) units with β-(1,4)-xylosidic linkages, with a degree of polymerization of 2–7 ( Kaur et al, 2023 ). Prebiotic properties of XOSs, including reduced blood cholesterol and colon cancer risk; increased calcium absorption, antioxidant effects, and intestinal functions; and the medical benefit of cytotoxic activity on human leukemia cells ( Amorim et al, 2019 ; Yegin, 2022 ).…”
Section: Introductionmentioning
confidence: 99%